The Effectiveness of Problem-Based Learning in Improving Fable Text Comprehension Among 5th Grade Elementary Students: A Classroom Action Research - Paujan Amris; Rahmat Kartolo; Sutikno (International Journal of Educational Research Excellence, 2026)
The background of this study is the low learning outcomes of students, primarily caused by conventional teaching methods that fail to actively engage learners. The Problem-Based Learning (PBL) model was chosen because it emphasizes collaborative, contextual, and independent problem-solving. The results revealed an improvement in student learning outcomes from cycle I to cycle II. In cycle I, the average pre-test score was 69.16, which increased to 73.33 in the post-test. The mastery level rose from 41.66% (8 students meeting the Minimum Mastery Criteria or KKM) to 66.6% (13 students achieving mastery). However, these results still fell short of the KKM benchmark of 75%. Therefore, revisions were made in cycle II. In this cycle, the average pre-test score rose to 81.6, and the post-test average reached 85.83. The mastery level increased to 83.3% (17 students), with certain indicators showing that 90% of students had reached or exceeded the KKM. This indicates a significant improvement in their understanding of content, moral messages, and the structure of fable texts. Moreover, students’ engagement also improved positively, particularly in aspects such as teamwork, the courage to express opinions, and discipline during group discussions. The implementation of the PBL model also enhanced teachers’ creativity in designing meaningful and engaging learning activities. Teachers acted as facilitators, while students took an active role in the learning process. This created a classroom atmosphere that was enjoyable, intellectually stimulating, and supportive of critical thinking development. Based on these findings, it can be concluded that the Problem-Based Learning model is effective in improving students’ comprehension of fable texts and is highly relevant for implementation within the Kurikulum Merdeka, which emphasizes differentiated, student-centered learning